Academic Self-Efficacy influencd is seen in term of Learning Motivation - Berliana Amandha; Riska Ahmad (Universitas Negeri Padang, 2020)
Motivation for student learning by several factors, one of which is self-efficacy which refers to the belief in an individual's ability to be able to meet the situation that is being used by the individual. Students' confidence in their own abilities in carrying out learning activities is called academic self-efficacy. This study aims: (1) to describe the academic self-efficacy of students who have high learning motivation, (2) to describe the academic self-efficacy of students who have low learning motivation, (3) to describe the significant difference between the academic self-efficacy of students who have motivation study high and low. This type of research is comparative descriptive using the chi-square analysis technique. The research subjects were all students who had high and low learning motivation in grades VII and VIII at the SMP Pembangunan Laboratorium UNP. A sample of 146 people, selected using stratified random sampling technique. The instrument used was a questionnaire with a Likert scale. The findings of the study revealed that the academic self-efficacy of students who had high learning motivation at the SMP Pembangunan Laboratorium UNP was classified as high, there is no academic self-efficacy of students who had low learning motivation at the SMP Pembangunan Laboratorium UNP. And chi-squre analysis revealed that there was difference between the academic self-efficacy of students who had high and low learning motivation at the SMP Pembangunan Laboratorium UNP.